THE PHILOSOPHICAL ANALYSIS OF THE UNDERSTANDING OF GOD WRATH AT ANY TIME BASED ON PSALM 7:12 INCONGREGATION OF INDONESIA PUBLISHING HOUSE (IPH) BANDUNG - Maropapa Sitorus; Stimson B. Hutagalung (Fakultas Filsafat Universitas Advent Indonesia, 2018)
The fundamental reason for this research is to analyze the opinion of king Davidabout God Wrath Every time based on Psalm 7:12. In this case, to understandthe spiritual meaning contained in Psalm 7:12 from king David's statement aboutGod through his personal experience. Therefore, the author uses three indicatorsto find the understanding of God Wrath Every Time. Every indicator that writeruse is; (1) The Meaning of God Wrath Every Time, (2) The reason that GodWrath Every Time, (3) The purpose that God Wrath Every Time. Nex Stept, isto find out the level of understanding from the members of the IndonesiaPublishing House (IPH) congregation about God Wrath Every Time.The methodology of this research consists of field data collection techniques,place and time of research, research results and methods of data analysis andresults and discussion.The meaning of God Wrath Every Time is because sin always against His natureor will. This shows God's attitude that unchanging toward a human who againstHim by breaking His law.God's wrath every time aims for believers to be comforted that evil does notescape from the observation of God. In this case, God is not being indifferent,in which there is goodness, justice, mercy, preventing the destruction of sinnersby bringing the sinner to repentance. At the same time God shows the necessityof doing judgments to sinners even the punishment of the unconverted.